2013
DOI: 10.29079/vol12iss1art237
|View full text |Cite
|
Sign up to set email alerts
|

Study of some minerals deficiency in grazing sheep in Thi-Qar Province

Abstract: This study was carried out on 250 locally sheep collected from four sides of Thi-Qar Governorate. The clinical, hematological, trace elements changes in naturally occurring minerals deficiency in sheep were described. Anemia & Pale mucous membranes, Alopecia &steely wool, Diarrhea, parakeratosis, pica and abortion constituted the main signs and symptoms. The respiratory and heart rates were significantly higher (p<0.05) in mineral deficient sheep than in normal control sheep in one side of province. Values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This also came along with Spears et al (2008), who recorded that the early sign of dark wool depigmentation may also be seen in case of copper deficiency. It was recorded in our study that copper deficiency associated with alopecia as well as decreased wool production and this agreed with Niekerk et al (1989) The result agreed with White (2004), Ali et al (2012) and Mohammed et al (2013), who reported that loss of wool appearance of alopecia in sheep with copper deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…This also came along with Spears et al (2008), who recorded that the early sign of dark wool depigmentation may also be seen in case of copper deficiency. It was recorded in our study that copper deficiency associated with alopecia as well as decreased wool production and this agreed with Niekerk et al (1989) The result agreed with White (2004), Ali et al (2012) and Mohammed et al (2013), who reported that loss of wool appearance of alopecia in sheep with copper deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Biochemically, roundworm infection in sheep and goats decreases copper absorption resulting in decline of copper concentration in serum (3) Copper plays an important role in regulating the mechanisms of different enzymes, particularly metabolic enzymes (4). Copper deficiency may cause dysfunction in reproductive, digestive, nervous, immune performance, and cardiovascular systems (5,6). Therefore, copper deficiency results in several clinical signs including anemia, diarrhea, poor wool production, and trembling (7).…”
Section: Introductionmentioning
confidence: 99%